Optimisation of the thermoelectric efficiency of zirconium trisulphide monolayers through unixial and biaxial strain. Issue 11 (20th October 2020) - Saiz, Fernan; Carrete, Jesús; Rurali, Riccardo
Abstract : The goal of this work is to investigate the influence of mechanical deformation on the electronic and thermoelectric properties of ZrS3 monolayers. Abstract : The goal of this work is to investigate the influence of mechanical deformation on the electronic and thermoelectric properties of ZrS3 monolayers. We employ density functional theory (DFT) calculations at the hybrid HSE06 level to evaluate the response of the electronic band gap and mobilities, as well as the thermopower, the electrical conductivity, the phononic and electronic contributions to the thermal conductivity, and the heat capacity. Direct examination of the electronic band structures reveals that the band gap can be increased by up to 17% under uniaxial strain, reaching a maximum value of 2.32 eV. We also detect large variations in the electrical conductivity, which is multiplied by 3.40 under a 4% compression, but much smaller changes in the Seebeck coefficient. The effects of mechanical deformation on thermal transport are even more significant, with a nearly five-fold reduction of the lattice thermal conductivity under a biaxial strain of −4%. By harnessing a combination of these effects, the thermoelectric figure of merit of strained ZrS3 could be doubled with respect to the unstrained material.